VARIASI JENIS KEMASAN DAN LAMA PENYIMPANAN PADA SUHU INGIN TERHADAP KADAR VITAMIN C DAN DAYA TERIMA JAM ROSELLA (Hibiscus sabdariffa) - Dewi Kumalasari; Nurhidajah - (Universitas Muhammadiyah Semarang, 2011)
As a perishable commodity Rosella flower require treatment to extend the shelf life time, which is the processing, packaging and storage. Rosella processing became Jam can extend the shelf life time and add a variety of diversification rosella and value added of economic. The results do not affect the type of packaging toward vitamin C (P value 0.724),whereas storage can effect on vitamin C because p-value <0.05 (0.000).The longer of storage timeRosella Jam result inthe vitamin C concentration will decrease. Vitamin C concentration ranged between 61.36-38.03 mg%. Organoleptic test results: 10-day storage the preference panelists still high when compared to the 15 days of storage.